2015
DOI: 10.1017/s0022215115003345
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cochlear implantation and labyrinthectomy for advanced Ménière's disease

Abstract: Surgical labyrinthectomy is effective for the elimination of vertigo in Ménière's disease patients. The major disadvantage in the past was loss of residual hearing. Cochlear implantation is now an option in these patients. The benefits of simultaneous labyrinthectomy with cochlear implantation include the prevention of implantation of a fibrosed or ossified cochlea, a decrease in the duration of deafness, and a single operative procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…Investigations of cochlear implantation in Meniere's disease patients have demonstrated successful auditory rehabilitation in this and other studies. 24,26,27 Simultaneous labyrinthectomy and cochlear implantation provides many benefits, including the benefit of an ablative and restorative procedure under a single general anesthetic, restoration of binaural hearing, and the potential elimination of vertigo and tinnitus. Notably, all of our patients had complete resolution of their tinnitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations of cochlear implantation in Meniere's disease patients have demonstrated successful auditory rehabilitation in this and other studies. 24,26,27 Simultaneous labyrinthectomy and cochlear implantation provides many benefits, including the benefit of an ablative and restorative procedure under a single general anesthetic, restoration of binaural hearing, and the potential elimination of vertigo and tinnitus. Notably, all of our patients had complete resolution of their tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigation of outcomes following simultaneous labyrinthectomy and cochlear implantation in Meniere's disease patients have either been retrospective case studies, focused on bilateral disease, or part of a larger cohort. 26,28,29 It is therefore difficult to apply any conclusive outcomes within the current literature to this study population. In our study, we aimed to prospectively investigate outcomes of speech perception, sound localization, and quality of life measures in subjects with unilateral Meniere's disease and normal or near-normal hearing in the contralateral ear following concurrent labyrinthectomy and cochlear implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, in a comparative study [53] between cochlear sacculotomy techniques and endolymphatic sac decompression, the control of vertigo was significantly better in patients after cochleo-sacculotomy but also with significant deterioration of hearing. The cochleo-sacculotomy procedure performed simultaneously with cochlear implant surgery in patients with deafness and persistent vertigo in Ménière's disease is an alternative already proposed by some authors [54][55][56], and they have reported good results.…”
Section: Sacculotomymentioning
confidence: 99%
“…For patients with single-sided Meniere's disease and profound sensorineural hearing loss, a simultaneous labyrinthectomy and cochlear implantation are efficient method for the treatment of vertigo and rehabilitation of the auditory system [40].…”
Section: Labyrinthectomymentioning
confidence: 99%